2014
DOI: 10.1097/inf.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Occurrence of Human Metapneumovirus Infections in Croatia

Abstract: This study indicates that HMPV infections in Croatia show a biennial outbreak pattern characterized by alternation of winter and spring activity. HMPV outbreaks alternate with respiratory syncytial virus outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
3
6
1
Order By: Relevance
“…The present study provides insights into the molecular epidemiology and genetic variability of HMPV circulating in Croatia between April 2011 and March 2014. Our data is consistent with previous observations showing trend of high and low incidence of HMPV in alternating years (biennial pattern: larger winter and smaller spring outbreaks) in hospitalized patients . The majority of HMPV infections were detected in the cold period of the year which is similar to previous reports for temperate climate countries .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study provides insights into the molecular epidemiology and genetic variability of HMPV circulating in Croatia between April 2011 and March 2014. Our data is consistent with previous observations showing trend of high and low incidence of HMPV in alternating years (biennial pattern: larger winter and smaller spring outbreaks) in hospitalized patients . The majority of HMPV infections were detected in the cold period of the year which is similar to previous reports for temperate climate countries .…”
Section: Discussionsupporting
confidence: 93%
“…Our data is consistent with previous observations showing trend of high and low incidence of HMPV in alternating years (biennial pattern: larger winter and smaller spring outbreaks) in hospitalized patients. 12,[26][27][28][29] The majority of HMPV infections were detected in the cold period of the year which is similar to previous reports for temperate climate countries. [30][31][32] The winterspring HMPV occurrence is traditionally regarded as the typical pattern of HMPV infections in the temperate regions, however, seasonal peaks observed from May to July of 2011 and April to July in 2013 are unusual, and such pattern is typically seen in tropical countries.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study conducted in Bangladesh reported a similar prevalence (4%) of hMPV infection . This finding also aligns with the proportion of hMPV‐positive cases reported in the studies conducted in Hong Kong (5.5%), USA (6.2%), Croatia (7%), and Finland (8%) . The proportion of hMPV‐positive swabs that were also found to be positive for other respiratory viruses was 9.2%, which is similar to what has been previously reported in epidemiological studies conducted in Japan, Hong Kong and Canada in different combinations of other respiratory viruses .…”
Section: Discussionsupporting
confidence: 89%
“…Although our samples originate from a short period of time (September 2011-January 2014), they distinctly indicate biennial occurrence of HPIV1, as we previously found for respiratory syncytial virus (RSV) and human metapneumovirus (HMPV) in Croatia (Ljubin-Sternak et al, 2014;Mlinarić -Galinovic et al, 2012). Biennial circulation of HPIV1 has also been reported in previous epidemiological studies (Fry et al, 2006;Morgan et al, 2013;Villaran et al, 2014;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 92%